A demand forecast study of a conventional meter of an electricity distributor - Resende, Ellen Werneck; Nazaré, Tiago Bittencourt (Brazilian Journal of Production Engineering, 2022)
Identifying customer demand forecasts can be understood as a major challenge for companies. It is up to them to improve their methods to predict this demand in order to serve their customers with satisfactory quality and avoiding excessive inventories. In this perspective, the objective of the present study was to carry out a case analyzing historical data of a conventional meter from January 2019 to June 2022. Methods such as qualitative interviews and benchmarking with suppliers and application of samples in statistical software were used, the Maple. At the end of the analysis of the results, a forecast of demand for the material was obtained until the year 2030. It was observed that it presents decreasing consumption, while the GD meter, which replaces it in the distributed generation connections, presents, between the years 2028 and 2029, consumption higher than conventional.
Keywords: Inventory; Meter; Consumption; Demand Forecast